Impact of environmental pollution on carboxyhemoglobin levels among smoking and non-smoking motorcycle taxi drivers (Bioscience Journal, 2018)
Studies related to environmental pollution, carbon monoxide levels and smoking need to be deepened, especially in the case of traffic workers. Therefore, the objective was to verify the association between environmental carbon monoxide and carboxyhemoglobin levels among smoking and non-smoking motorcycle taxi drivers. A longitudinal epidemiological study was carried out with 95 motorcycle taxi drivers with measurement of the environmental carbon monoxide, carboxyhemoglobin in the exhaled air in three moments with interval of six months, between June 2014 and March 2015, as well as sociodemographic and occupational characteristics of these workers. The seasons of the year presented different carbon monoxide averages (p